Experiences Around the Clauses: A Transitivity Analysis of Four Famous People’s Suicide Notes - Sawirman Sawirman; Nurul Huda Ridhwani (Vivid: Journal of Language and Literature, 2020)
Four suicide notes written by three famous people, Jiah Khan, Kevin Carter, and Virginia Woolf, were analyzed in this study. Systemic Functional Linguistics theory especially about transitivity proposed by Halliday is used to see the ideational meaning of all four suicide notes by identifying the elements of the clauses. This study was conducted with a qualitative method assisted by a descriptive statistical method to see the spread and functions of the elements of transitivity in the suicide notes. To analyze the text based on the theory of transitivity, the text is divided into clauses based on the type of process, then each element of the existing process, participant, and circumstantial element is calculated. The results show that out of 170 total processes found, the material process (42.94%) is the most dominant process, followed by the mental process (28.82%), the relational process (19.41%), the verbal process (5.29%), the behavioral process (2.94%), and the existential process (0.59%). Just like the process type, from the two types of participants (who are directly involved and obliquely involved) that exist, actor (22.88%) and scope (15.36%) which are the participants of the material process are the most dominant participants. While the existent (0.31%) which is the participant of the existential process, has the lowest occurrence frequency. For the circumstantial element, location which consists of place and time is the most dominant circumstantial element. The location accounts for 44% of the circumstantial elements in all four suicide notes. Furthermore, Jiah Khan’s suicide note with the material process as the most dominant process describes the unpleasant behavior she experienced, which then leads to betrayal, sacrifice, self-destruction, loss, and loneliness. Whereas Kevin Carter’s suicide note with the relational process of attributive as the most dominant process describes regret, pressure, and despair. Then both Virginia Woolf’s suicide notes show how she blamed herself for what happened although it has different dominant processes between the first suicide note and the second suicide note.